2016
DOI: 10.1016/j.neuropsychologia.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

A matter of attention: Crossmodal congruence enhances and impairs performance in a novel trimodal matching paradigm

Abstract: A novel crossmodal matching paradigm including vision, audition, and somatosensation was developed in order to investigate the interaction between attention and crossmodal congruence in multisensory integration. To that end, all three modalities were stimulated concurrently while a bimodal focus was defined blockwise. Congruence between stimulus intensity changes in the attended modalities had to be evaluated. We found that crossmodal congruence improved performance if both, the attended modalities and the tas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…This was achieved by estimating detection thresholds for each modality and change direction separately using a psychophysical staircase procedure 29 . Yet, a questionnaire that was completed during debriefing of the preceding behavioural study 16 indicated that subjective salience of the sensory components when presented jointly was in fact not equal, but strongest for the visual component. In particular, participants reported that the visual component was hardest to ignore when it was task irrelevant (Wilcoxon rank sum test, Bonferroni correction; average ranks: V = 1.4, A = 2.3, T = 2.1; V-T: p corr = 0.0074, V-A: p corr = 0.7902, T-A: p corr = 0.7200).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was achieved by estimating detection thresholds for each modality and change direction separately using a psychophysical staircase procedure 29 . Yet, a questionnaire that was completed during debriefing of the preceding behavioural study 16 indicated that subjective salience of the sensory components when presented jointly was in fact not equal, but strongest for the visual component. In particular, participants reported that the visual component was hardest to ignore when it was task irrelevant (Wilcoxon rank sum test, Bonferroni correction; average ranks: V = 1.4, A = 2.3, T = 2.1; V-T: p corr = 0.0074, V-A: p corr = 0.7902, T-A: p corr = 0.7200).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to stimulus-driven aspects of multisensory perception, a multitude of studies show behaviourally beneficial effects of concurrent and congruent multisensory stimuli 1416 . While this is well established, underlying mechanisms remain largely elusive 1719 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the sense of touch has been shown to be immensely important in all areas of everyday life (Gallace and Spence, 2014). Furthermore, there is evidence suggesting that tasks involving the interaction of visual and somatosensory stimuli profit strongly from crossmodal interaction effects (Mahoney et al, 2011;Misselhorn et al, 2016). The tactile modality interacts with vision for example in object recognition or the identification of somatosensory stimuli but also in posture control (Tipper et al, 1998;Oie et al, 2002;List et al, 2012;Gallace and Spence, 2014).…”
Section: Introductionmentioning
confidence: 99%